POST-OPERATIVE PORT SITE PAIN AFTER GALL BLADDER RETRIEVAL FROM EPIGASTRIC VS UMBILICAL PORTS IN LAPAROSCOPIC CHOLECYSTECTOMY - SHAFIQ, M; KUMAR, R; JABEEN, S; IQBAL, M; ALI, A; LAKDAWALA, Y (Biological and Clinical Sciences Research Journal, 2024)
Laparoscopic cholecystectomy (LC) is a widely performed procedure for gallstone disease. While epigastric and umbilical ports are commonly used for gallbladder retrieval, their comparative impact on postoperative discomfort, complications, analgesic requirements, and hospital stay remains underexplored. Identifying the optimal port site can improve patient outcomes and safety. Objective: The purpose of the present study was to assess postoperative discomfort, analgesic requirements, complication rates, and duration of hospitalization in patients undergoing LC with gallbladder retrieval either through the epigastric or the umbilical port in order to draw a conclusion on which port site offers better results in terms of patient comfort and safety. Methods: After the ethical approval from the institutional review board, this randomized controlled trial study was conducted at FRPMC PAF hospital from August 2023 to July 2024. Through non-probability consecutive sampling, 100 patients aged 18-65 years, of both gender, diagnosed with gallstones confirmed with ultrasound were included in the present study. Patients with suspected or proven G.B malignancy, coagulation disorder, obstructive jaundice, acute pancreatitis or emergency cases were excluded from the present study. After the informed consent, patients were randomly divided in to two groups: Group A- Epigastric port site (n=50) and Group B- Umbilical port site (n=50). Results: By 12 hours, the epigastric port group had a lower mean pain score of 4.14±3.04 compared to 5.4±3.3 in the umbilical port group (P=0.056). Analgesic requirements were also similar between the groups, with the epigastric port group requiring an average of 93.6±56.6 mg and the umbilical port group 99.96±55.3mg, yielding a p-value of 0.507. Complications were significantly more common in the epigastric port group, with 29 patients (58%) experiencing complications compared to 19 patients (38%) in the umbilical port group, and a p-value of 0.032. Conclusion: The selection of the port in laparoscopic cholecystectomy does not seem to be critical regarding the duration of either surgery or hospitalization; however, an increased complication rate and trends of postoperative pain do underline the importance of port selection.